Peningkatan Keberdayaan Ekonomi Melalui Pengelolaan Limbah Organik dan Pertanian Terpadu di Lahan Terbatas - Turista, Dora Dayu Rahma; Kurniawati, Zenia Lutfi; Putra, Gisky Andria; Anwar, Yaskinul; Rahmawati, Indah; Rosinta, Rosinta; Rabbani, Muhammad Abid; Setiawan, Volta Kellik (Universitas Nusantara PGRI Kediri, 2025)
Agricultural practices on limited land using organic waste management byproducts pose a significant challenge, especially in Lempake Village, North Samarinda. Bank Ramli Bukit Benanga in RT 037 Bukit Benanga Housing has successfully converted organic waste into eco enzyme, compost, and maggot, though these products have not been optimally utilized or marketed. This Community Partnership Program aims to empower the community by enhancing skills in integrated agriculture on limited land and facilitating the marketing of organic products from constrained spaces. Through training and mentoring in aerofarming, tabulampot, and budikdamber techniques, the program aims to utilize eco enzyme, compost, and maggot more effectively in plant and fish cultivation. It also equips partners with packaging design skills and strategies for online and offline marketing. The program results include increased independent food production, enhanced partner income through organic product marketing, and improved environmental quality around Bukit Benanga Housing. Additionally, the program supports the Sustainable Development Goals (SDGs), particularly in poverty reduction, welfare improvement, and sustainable production and consumption patterns.